Skrining Fitokimia dan Uji Aktivitas Antioksidan Pelepah Batang dan Bunga Pisang Kepok (Musa acuminatae, L.) - Farisya Nurhaeni (Politeknik Kesehatan Bhakti Setya Indonesia, 2019)
One of the natural ingredients whose benefits are not widely known is the stem and flower of the kepok banana (Musa acuminatae, L.). Stems and flowers of the banana are known to contain flavonoid compounds. Most of the flavonoid compounds have antioxidant activity. This study aims to determine the antioxidant activity and to perform phytochemical screening of the stem and flower ethanolic extracts from banana kepok. Simplicia powder from stem and banana flower was extracted by remaceration method using 96% ethanol. The extract was then tested for antioxidant activity by spectrophotometer using the DPPH method (2,2-diphenyl-1-picrylhydrazyl) at a wavelength of 520 nm. The standard compound used for comparison is quercetin. The results showed that the IC50 value for the ethanol extract of the stem was 19,75 µg/ml and the kapok flower of banana was 13,21 µg/ml . The results of phytochemical screening showed that the stem and flower of banana kepok extract contained flavonoid, saponin and polyphenol.